The darkness outside us - Schrefer, Eliot, 1978- (Katherine Tegen Books, 2022)
With no memories of how he got there, seventeen-year-old Ambrose wakes up on the spaceship "Coordinated Endeavor" to discover he's on a mission to save his sister with an enemy named Kodiak from the warring country Dimokratía. With the ship's operating system guiding them, Kodiak and Ambrose both realize the operating system isn't telling them everything. As they work to piece together their lost memories, a romance develops between them and they learn that they will need to trust each other if their mission is to succeed.